Estudo experimental de efeitos de spin em heteroestruturas semicondutoras - Gordo, Vanessa Orsi (2015)
In this thesis, we have investigated optical and spin properties of semiconductor nanostructures. Photoluminescence and magneto-photoluminescence measurements were performed in high magnetic field (B ≤ 15T), in GaBiAs nanostructures and GaAs /AlGaAs semiconductor devices. Particularly, we have studied: (i) GaBiAs layers, (ii) GaBiAs/GaAs quantum wells (QW) (iii) standard GaAs / AlGaAs resonant tunneling diodes (RTDs) and (iv) GaAs / AlGaAs RTDs containing quantum rings of InAs in the QW. We have investigated the effect of carrier localization by defects on the optical and spin properties of GaBiAs layers and nanostructures. Our results evidence important effects of carrier location by defects which was associate by small values of magnetic shifts. This effect is probably due to the formation of clusters and by the Bi composition variation on this type of alloy. It was also observed that the thermal annealing treatment improves the optical quality of these systems and increases the polarization degree which was associated to the reduction of spin relaxation times. We have also investigated the optical properties, magneto-optical and of transport in double barrier semiconductor heterostructures. Particularly, we have investigated the optical and spin properties of two dimensional electron and hole gases and the quantum well (QW). It was observe optical emission in the QW associate to the criation of uncharged exciton and negative charge exciton. The two dimensional gases acts as a spin polarize carriers injection in the QW, increasing thus the spin polarization in this region. The experimental results indicated that this process is more efficient in low voltage region. For high voltages region other processes, such as formation of tríons and spin polarization loss during tunneling should result in a significant contribution to the spin and polarization. Furthermore, it was investigated the spin properties of double barrier diodes containing InAs quantum rings in the center of the QW. It was observe that the degree of circular polarization of the emission of the QRs strongly sensitive to the applied voltage shows oscillation and besides one possible polarization oscillations tendency with the increase of the magnetic field.